Enhanced therapeutic index of liposomal doxorubicin Myocet locally delivered by fibrin gels in immunodeficient mice bearing human neuroblastoma. (January 2021) - Viale, Maurizio; Bertone, Vittorio; Maric, Irena; Cilli, Michele; Emionite, Laura; Bocchini, Vittorio; Ponzoni, Mirco; Fontana, Vincenzo; De Luca, Fabrizio; Rocco, Mattia
Graphical abstract: Highlights: Fibrin gels (FBGs) are well-known vehicles for the local delivery of drugs. Caelyx and Myocet are effective liposomal doxorubicin formulations (LDF). Toxicity/anti-tumor activities of LDF released by FBGs were studied in mice. Myocet-FBGs had a better therapeutic index than free Dox iv or Caelyx-FBGs. Myocet-FBGs represents a possible new tool for human neuroblastoma treatment. Abstract: Caelyx and Myocet are clinically used liposomal forms of doxorubicin (Dox). To explore ways to improve their therapeutic index, we have studied their activity in vitro and in vivo when locally delivered by fibrin gels (FBGs). In vivo local toxic and anti-tumour activities of loaded FBGs were assessed in two immunodeficient mouse orthotopic human neuroblastoma (NB) models after application in the visceral space above the adrenal gland, either still tumour-bearing or after tumour removal. In parallel, in vitro assays were used to mimic the in vivo overlaying of FBGs on the tumour surface. FBGs were prepared with different concentrations of fibrinogen (FG) and clotted in the presence of Ca 2+ and thrombin. The in vitro assays showed that FBGs loaded with Myocet possess a cytotoxic activity against NB cell lines generally greater than those loaded with free Dox or Caelyx. In vivo FBGs loaded with Myocet showed lower general and local toxicities as compared to gels loaded with Caelyx or free Dox, and also to free Dox administered i.v. (all treatments with Dox at 2.5 mg/Kg). The anti-tumour activity, evaluated in the two mouse orthotopic NB models of adjuvant and neo-adjuvant therapy, resulted in a better performance of FBGs loaded with Myocet compared to the other local (FBGs loaded with Caelyx or free Dox) or systemic (free Dox) treatments (administered at 2.5 and 5 mg/Kg Dox). Specifically, the application of FBGs at 40 mg/mL in the adjuvant model caused 92 % tumour volume reduction, while by the neo-adjuvant application of FBGs at 22 mg/mL a re-growing tumour volume reduction of 89 % was obtained. Taken together, our in vitro and in vivo results indicate a significantly higher activity for the FBGs loaded with Myocet. In particular, the lower toicity coupled with the higher anti-tumour activity on both the local treatment modalities strongly suggest a better therapeutic index when Myocet is administered through FBGs. Therefore, FBGs loaded with Myocet may be considered as a possible new tool for the loco-regional treatment of NB or even other tumour histotypes treatable by loco-regional chemotherapy.